TRADISI JUAL BELI ANAK DI KABUPATEN PADANG PARIAMAN PERSPEKTIF AL-‘URF DAN HUKUM PIDANA - Hidayat, Taufik; Amir, Yusri; Yazid, Yovidal; Fansuri, Arif (Institut Agama Islam Negeri Batusangkar, 2019)
The tradition of ?buying and selling? children in the community of Padang Pariaman Regency is a habit that has been passed down for generations. Though Islamic law and Indonesian criminal law forbid ?buying and selling? children. This research is an empirical legal research by looking at the phenomenon of the tradition of ?buying and selling? children in Padang Pariaman Regency. Then, it was analyzed with al-'urf in Islamic law and elements of criminal acts in Indonesian criminal law. Based on the results of research that the purpose of the tradition of ?buying and selling? children in Padang Pariaman Regency is to eliminate the bad luck of a child by his biological parents. This in Islamic law belongs to al-furf al-fasid. So that despite the sale and purchase of children in Padang Pariaman Regency, this tradition is not included in the crime of trafficking of children, because it does not fulfill the elements of the crime of child trafficking.